The effect of arthroscopic rotator cuff repair on golf handicap - Jordan K. Penn, BS; Alex Friedman, DO; Mateo L. Pacelli; Daniel T. Keefe, MD; Brian J. Rebolledo, MD; Jan Fronek, MD; Laura R. Alberton, MD; Heinz R. Hoenecke, MD (JSES International)
Background: Golf is a popular sport worldwide that has been embraced by individuals of all ages. In middle-aged and older golfers, shoulder pain during sport can be associated with rotator cuff (RC) pathology given the complex coordination required to swing a golf club. Patients considering arthroscopic RC repair often ask how their golfing ability will be affected by surgery. The purpose of this study was to assess golf handicap as a measure of golfing ability among patients who underwent arthroscopic RC repair. Methods: Twenty-nine patients who underwent arthroscopic RC repair between 2017 and 2020 were retrospectively identified. All patients indicated that they played golf before and after surgery and provided their golf handicap information network number so that their handicap data could be obtained. Indications included complete tear (n = 22) and partial tear (n = 7) of the RC that required repair. Mean age was 65 ± 8.1 years, and 97% were males. Golf handicap was compared between the most recent handicap preoperatively (within 1 year prior to surgery) and 1 and 2 years following surgery. Eighteen of 29 patients were available for telephone interviews at a mean of 5.6 ± 1.2 years to capture additional handicap data and outcomes including the American Shoulder and Elbow Surgeons Shoulder score and the Single Assessment Numeric Evaluation. Results: Handicap increased by 1.2 strokes 1 year after surgery (P = .007). By 2 years postoperatively, no change from preoperative handicap was seen (P = .107). Change in handicap between patients who had surgery on their lead vs. back shoulder did not vary significantly at 1 year (P = .688) or at 2 years (P = .184) after surgery. Discussion: Arthroscopic RC repair led to a decrease in golfing ability 1 year after surgery but returned to preoperative ability by 2 years after surgery.